Gênero na construção civil : um estudo de caso sobre as trabalhadoras da Norcon - Araújo, Fernanda Oliveira de (2005)
The present study tried to reveal how the values absorbed by the female servants of the production sector of NORCON influence their work, taking into account that they were acquired through various social processes responsible for the learning of attributes, competences, qualifications, and through determined roles within the social and sexual division of work. In order to do so, the following categories were used: work; gender; construction of gender identity; qualification of gender; public/private aiming at adopting a critical view in the gender approach as a key analytical category in the analysis of the problem. The data collection techniques used were questionnaires and testimonies, since they seemed more appropriate to collect relevant data to the development of the study. In the final thoughts, it was concluded that the insertion of women in such a male-dominant sector reveals contradictions since it is a victory that goes forth to the acquisition of full citizenship but at the same time women are allocated in activities in which qualification took place in a subjective form, through the process of socialization acquired in the family space and in other institutions.